Eliciting initial programme theories for a health research capacity strengthening initiative targeting African universities: A realist synthesis - Meshack Nzesei Mutua; Andrew Harding; Ferdinand C. Mukumbang; Justin Pulford (PLoS ONE, 2025)
There is a growing call for theory-driven evaluation approaches to health research capacity strengthening (HRCS) interventions. Specifically, realist evaluation has gained wide attention given its response to the question: How does an intervention work, why, for whom and under what conditions? In realist evaluation, initial programme theories (IPTs) are first elicited before they are tested and refined. This article describes the IPTs of an HRCS programme aimed at strengthening the research capacity of African universities. Using the ‘Developing Excellence in Leadership, Training and Science (DELTAS Africa) programme as a real-world case, the IPTs were drafted through a review of the programme documents and other published literature. Seven programme documents and 32 published papers covering 26 research capacity strengthening initiatives in African universities were reviewed. Different Context, Mechanism and Outcomes (CMO) were extracted and CMO configurations were formulated. Thereafter, the CMO configurations were refined through four interviews with the DELTAS programme designing team. Three transferrable IPTs were elicited. Evidence suggests that, for HRCS interventions to be more effective in strengthening research capacity in African universities, systemic challenges (e.g., lack of funding for health research, ineffective research policy environment and lack of institutional support for research) need to be addressed and the university staff/ researchers empowered, incentivised and motivated. The article underscores the importance of institutional buy-in, effective implementation of research policies (e.g., protected time, research career pathways, gender equality, research ethics and integrity, anti-bullying and anti-harassment, etc.), long-term research funding and equitable research partnerships in fostering a strong research environment and culture. Notably, the article makes a methodological contribution by demonstrating how IPTs can be developed using disparate evidence sources. The IPTs will be tested and refined through a primary realist evaluation, which will further refine the CMOs presented in this article and provide insights into the current HRCS evaluation framework.